2019
DOI: 10.1016/j.foodres.2018.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of intestinal microbiota and immunometabolic parameters by caloric restriction and lactic acid bacteria

Abstract: Modulation of intestinal microbiota and IMMUNO-metabolic parameters by caloric restriction and lactic acid bacteria. Frin (2017),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…This peptide acts promoting the proliferation of proinflammatory cells and cytokines, like TNF-α and IL-6. The immunomodulatory probiotic CRL431 previously showed to raise leptin levels in mice under a caloric restriction diet (16). In general, it is expected that positive impacts of probiotics on obesity and associated metabolic disorders are related to a decrease in serum leptin values or leptin expression (10,38,39).…”
Section: Discussionmentioning
confidence: 99%
“…This peptide acts promoting the proliferation of proinflammatory cells and cytokines, like TNF-α and IL-6. The immunomodulatory probiotic CRL431 previously showed to raise leptin levels in mice under a caloric restriction diet (16). In general, it is expected that positive impacts of probiotics on obesity and associated metabolic disorders are related to a decrease in serum leptin values or leptin expression (10,38,39).…”
Section: Discussionmentioning
confidence: 99%
“…In the Firmicutes phylum, several studies assessed the impact of 25-40% CR based on a normal ad libitum diet and showed an increase of Lactobacillaceae [16,94], such as Lactobacillus spp. [17][18][19][20][21][22], Erysipelotrichaceae [16,94], and Ruminococcaceae [94] in CR rodents compared with normal-diet rodents. Conversely, a decrease of Lactococcus spp., [22], Lachnospiraceae [22,95] and Clostridiales [94,95] was found in CR rodents compared with controls.…”
Section: Caloric Restriction (Cr) and Gut Microbiota Variationsmentioning
confidence: 98%
“…CR could also impact the composition of Bacteroidetes, increasing the abundance of Bacteroidaceae [16,17,20,21,94], Proteobacteria [17,21,22,96], and Verrucomicrobia [16,96] with an increase of Akkermansia muciniphila counts [16]. In the Actinobacteria phylum, in several studies [17,[20][21][22], counts of some Bifidobacterium spp. increased in CR animals compared with normal diet-fed animals.…”
Section: Caloric Restriction (Cr) and Gut Microbiota Variationsmentioning
confidence: 99%
See 2 more Smart Citations